Study of Genetic Diversity in South Indian Taro (Colocasia esculenta (L.) Schott.) Using Random Amplified Polymorphic DNA Markers - Beevi, P. Nusaifa; Sreekumari, M.T.; Kumar, Vijayaraghava (JOURNAL OF ROOT CROPS, 2013)
Sixty accessions of taro (Colocasia esculenta (L.) Schott.), collected from the three South Indian states were analyzed using nine Random Amplified Polymorphic DNA (RAPD) primers at Central Tuber Crops Research Institute, Thiruvananthapuram, Kerala, India. The results obtained were utilized for assessing the extent and pattern of intraspecific variation within the species complex. Out of the nine primers, four proved to be highly informative as they could detect high levels of polymorphic fragments and were able to differentiate the accessions. The phylogenetic tree generated using UPGMA cluster analysis revealed that genetic diversity in taro was correlated with the wild and the cultivated forms. The accessions were separated into five major clusters. Out of the five clusters obtained in the dendrogram at 40% level of similarity coefficient, cluster I and cluster II included mainly cultivars. Cluster IV included almost exclusively wild accessions, majority of them being true wild ones with frequent flowering and significant stolon production. The primers were able to distinguish between diploids/triploids accessions. The diploid (clusters I, II, III and IV) and triploid (cluster V) group of accessions tended to form independent clusters and this may be suggestive of agro-ecological and sexual separation between them. These primers will be useful for future genetic analysis and provide taro breeders with a genetic basis for selection of parents for crop improvement programmes.